Characteristics of interior noise of a Chinese high-speed train under a variety of conditions - Zhang, Jie; Xiao, Xin-biao; Sheng, Xiao-zhen; Fu, Rong; Yao, Dan; Jin, Xue-song (Journal of Zhejiang University. A. Science, 2017)
This paper presents an investigation into the characteristics of interior noise of a Chinese high-speed train under several typical conditions. Interior noises within Vehicle TC01, which can be used as a head car or an end car, and Vehicle TP03, the third car counting from TC01, are measured for the train running at speeds from 260 km/h to 385 km/h, along two types of track including a slab track and a ballast track and either on the ground surface or in a tunnel. Data analyses are performed for sound pressure overall levels, frequency, area contributions, and possible generation mechanisms, showing how they are affected by train speed, running direction, track type, and tunnel. The results show that, whether TC01 is used as head car or end car, the interior noise characteristics in the VIP cabin are mostly related to aerodynamic noise. Differences in interior noise between tracks become smaller as the train speed increases. The effect of a tunnel on the interior noise is more important for the middle coach than that for the head coach. This study can provide a basis for noise control of high-speed trains.